2014
DOI: 10.1016/j.jvs.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Routine use of completion imaging after infrainguinal bypass is not associated with higher bypass graft patency

Abstract: In our observational cohort, CIM does not improve short-term and 1-year bypass graft patency in infrainguinal LEB. The surgeon-specific strategy of selective CIM after LEB has outcomes comparable to those of routine CIM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…In addition, the VSGNE database has appropriately been used for a similar type of cutoff analysis in reference to outcomes after routine ($80%) vs selective (<80%) use of completion imaging studies during lower extremity bypasses. 22 We also recognize that the use of ultrasound and outcomes may vary across the centers. However, in a separate interventionalist-level analysis taking into account variability between the centers, we reached similar conclusions (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the VSGNE database has appropriately been used for a similar type of cutoff analysis in reference to outcomes after routine ($80%) vs selective (<80%) use of completion imaging studies during lower extremity bypasses. 22 We also recognize that the use of ultrasound and outcomes may vary across the centers. However, in a separate interventionalist-level analysis taking into account variability between the centers, we reached similar conclusions (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…2 The Vascular Study Group of New England (VSGNE) database, a regional quality group of the VQI, reported a somewhat higher CI rate of 67% in 2032 LEBs. 8 The lack of compliance with the textbook recommendation is likely related to the wide variation in the literature regarding the impact of CI on the patency of LEB, which was not examined in this study. Intraoperative completion arteriography findings have been proposed to correlate with risk of early graft failure.…”
Section: Discussionmentioning
confidence: 93%
“…15 The VSGNE study encompassed 2032 LEBs performed by 48 surgeons and included all conduit types, target arteries, and urgencies. No difference in discharge primary patency or 1-year primary patency was found for LEBs performed with and without CI.…”
Section: Discussionmentioning
confidence: 99%